How do nurse consultant job characteristics impact on job satisfaction? An Australian quantitative study - Michelle Giles; Vicki Parker; Rebecca Mitchell; Jane Conway (BMC, 2017)
Abstract Background There is a direct link between job satisfaction, nurses' job performance and improved patient outcomes. Understanding what job characteristics influence job satisfaction is vital if health organizations are to optimize individual employee satisfaction and performance. This is particularly necessary in the Nurse Consultant role, which is a multifaceted role that has evolved to meet the dynamic and changing needs of health services. This study aims to examine how job characteristics influence Nurse Consultant job satisfaction and identify differences across metropolitan and rural contexts. Methods This paper presents quantitative findings that are part of a larger prospective cross sectional mixed method study. An online survey consisting of a variety of job characteristic factors was administered to all NCs working in a large Local Health District in New South Wales, Australia over an 8-week period in 2010. Descriptive analysis identified NC's perceptions of job satisfaction and job characteristics in their current role and factor and regression analysis identified relationships between these factors. Results Job satisfaction was identified as high (mean 4.3) and is strongly correlated with job autonomy, role clarity, role conflict and job support. A high level of role clarity has a moderating effect on the relationship between job autonomy and job satisfaction. Conclusions Study findings inform how we prepare nurses for the NC role and how managers engage with and support NCs in their role taking into account context. Understanding the factors that influence job satisfaction and role effectiveness gives managers valuable information to assist in positioning and supporting these roles to maximize effectiveness across integrated and contemporary models of health care delivery.